2011
DOI: 10.3201/eid1709.110295
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Effect of Antiviral Drug Use during Pandemic (H1N1) 2009 Outbreak, United States

Abstract: From April 2009 through March 2010, during the pandemic (H1N1) 2009 outbreak, ≈8.2 million prescriptions for influenza neuraminidase-inhibiting antiviral drugs were filled in the United States. We estimated the number of hospitalizations likely averted due to use of these antiviral medications. After adjusting for prescriptions that were used for prophylaxis and personal stockpiles, as well as for patients who did not complete their drug regimen, we estimated the filled prescriptions prevented ≈8,400–12,600 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 18 publications
3
34
1
Order By: Relevance
“…We calculated the potential demand for NAIs across age groups (0–9, 10–19, 20–59, ≥60 years) for a range of pandemic scenarios using methods based on previous work [27]. To do so, we used assumptions regarding the clinical attack rate [22], the proportion of the population that would likely require treatment, seek medical care and be prescribed NAIs [25, 26], the number of regimens that may be dispensed for chemoprophylaxis or saved for a personal stockpile, and the proportion of those with non-influenza illness who may also receive NAI treatment [27].…”
Section: Methodsmentioning
confidence: 99%
“…We calculated the potential demand for NAIs across age groups (0–9, 10–19, 20–59, ≥60 years) for a range of pandemic scenarios using methods based on previous work [27]. To do so, we used assumptions regarding the clinical attack rate [22], the proportion of the population that would likely require treatment, seek medical care and be prescribed NAIs [25, 26], the number of regimens that may be dispensed for chemoprophylaxis or saved for a personal stockpile, and the proportion of those with non-influenza illness who may also receive NAI treatment [27].…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have suggested that aggressive treatment policies can effectively mitigate local transmission ( 16 , 17 ). In preparation for future influenza pandemics, the US Department of Health and Human Services therefore maintains a large Strategic National Stockpile (SNS) of antiviral drugs ( 18 ), and most states include SNS antiviral drugs as a major component of their pandemic response plans ( 19 – 22 ).…”
mentioning
confidence: 99%
“…The demographic variables that could affect the distribution of influenza A infections in populations are gender [16][17][18][19], age [15], clinical signs [20], vaccination against flu [21], usage of antimicrobials [22,24], smoking habits [25,29], and ethnicity [30,31].…”
Section: Introductionmentioning
confidence: 99%